Minimally Invasive Nasal Valve Treatment - Jones, Evan A.; Sivam, Sunthosh (Facial Plastic Surgery, 2022)
The objective of this article is to explore minimally invasive techniques to treat a poorly functioning nasal valve. It reviews the literature to introduce anatomy and examination, detail efficacy, instruct procedural protocols, and summarize utility. The article was composed based upon literature review and expert opinion. Nasal obstruction is a frequent problem managed by the facial plastic surgeon. It can occur at multiple sites, but commonly problematic regions are the nasal valves. A comprehensive nasal exam can elucidate the source of obstruction and validated obstruction measurements, such as the Nasal Obstruction Symptom Evaluation Instrument or the Standardized Cosmesis and Health Nasal Outcomes Survey for Functional and Cosmetic Rhinoplasty, can classify severity. Cartilage grafting and open septorhinoplasty techniques are invaluable for correcting nasal valve obstruction; however, the traditional methods may be neither possible nor optimal for all patients. Minimally invasive treatment modalities have emerged to offer an alternative to classical treatment algorithms. Minimally invasive techniques aimed at improving the nasal valve function include nasal dilators, suture suspension, lateral nasal wall bioresorbable implants, and cartilaginous radio frequency remodeling. Benefits of these methods include clinic-based intervention, avoidance of general anesthesia, use in previously operated noses, and minimally invasive nature. Publications with ranging levels of evidence support the efficacy of these interventions when patients with isolated nasal valve obstruction are examined. Limitations in the data, such as study power, source of funding, duration of follow-up, and longevity of response, warrant the need for further investigation; however, the efficacy of these techniques justifies implementation in proper patient populations into current practice. Minimally invasive nasal valve correction is a valuable tool in the armamentarium of the facial plastic surgeon. It cannot and should not replace traditional septorhinoplasty; however, the techniques are a valuable consideration for the appropriate patient population.
Keywords: nasal valve; nasal dilators; suture suspension; lateral nasal wall implant; radio frequency remodeling